Pengaruh Konsentrasi Kepemilikan dan Kompetensi Dewan Komisaris pada Manajemen Laba di Perusahaan Perbankan - Wirayana, I Made Adhi; Sudana, I Putu (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
This study aims to obtain empirical evidences concerning on the influence of ownership concentration and board of commissioner’s competence on earnings management. This research was undertaken on banking companies registered in Indonesian Stock Exchange from 2010 to 2015. Sampling method used was purposive sampling technique. There are 30 companies as data sample with total 180 observation. The data was accumulated with documentation method. Multiple linear regression test technique was used in analyzing the data. The finding of this study shows that institutional ownership has positive influence on earnings management while managerial ownership does not have any influence. Both board of commissioner’s competence of specifically business fields and corporate governance has negative influence on earnings management while Board of commissioner competency in accounting fields does not have any influence. Keywords: ownership concentration, competence, Earnings Management.